2023
DOI: 10.1021/acs.jmedchem.3c00948
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery Targeting Nuclear Receptor Binding SET Domain Protein 2 (NSD2)

Abstract: Nuclear receptor binding SET domain proteins (NSDs) catalyze the mono-or dimethylation of histone 3 lysine 36 (H3K36me1 and H3K36me2), using S-adenosyl-L-methionine (SAM) as a methyl donor. As a key member of the NSD family of proteins, NSD2 plays an important role in the pathogenesis and progression of various diseases such as cancers, inflammations, and infectious diseases, serving as a promising drug target. Developing potent and specific NSD2 inhibitors may provide potential novel therapeutics. Several NSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 274 publications
0
4
0
Order By: Relevance
“…41 Given these observations, researchers have extensively studied SETD2 inhibitors for their application in treating TNBC. 42 It deserves to be mentioned that breast cancer involves a myriad of other vital hPTMs beyond the target histone H3 methylations and acetylations explored in this study. For instance, phosphorylation represents another significant histone modification, which adds phosphate groups to histone proteins.…”
Section: ■ Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…41 Given these observations, researchers have extensively studied SETD2 inhibitors for their application in treating TNBC. 42 It deserves to be mentioned that breast cancer involves a myriad of other vital hPTMs beyond the target histone H3 methylations and acetylations explored in this study. For instance, phosphorylation represents another significant histone modification, which adds phosphate groups to histone proteins.…”
Section: ■ Discussionmentioning
confidence: 92%
“…Notably, mutations in histone methyltransferase SETD2, which is responsible for catalyzing H3K36me3, have been identified in TNBC . Given these observations, researchers have extensively studied SETD2 inhibitors for their application in treating TNBC …”
Section: Discussionmentioning
confidence: 99%
“…Cell-based studies confirmed the ability of 34 to bind into the NSD2-PWWP1 pocket; however, we were unable to demonstrate a functional inhibition of H3K36 demethylation. Potent, cell-permeable ligands such as 34 can potentially aid the development of alternative NSD2 inhibition strategies . For example, recent publications have described the chemical modification of NSD2 PWWP1 ligands into NSD2 protein degraders. , Future hybridization campaigns using 34 with some of the most active compound found through the FEP/ML approach, such as compounds 26 and 27 , might represent a further strategy for the identification of even more potent compounds with different physiochemical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Several small-molecule NSD2 inhibitors have been discovered to target either the SET domain ( 1 , 2 , 3 ) or PWWP1 domain ( 4 , 5 ) of NSD2 (Figure ). However, these inhibitors suffer from low activity or inferior selectivity. While compound KTX-1001, a novel NSD2-SET inhibitor developed by K36 Therapeutics, Inc., was advanced into phase I clinical trials to treat patients with relapsed and refractory multiple myeloma in 2022 (ClinicalTrials.gov identifier: NCT05651932), its structure and preclinical data have not been disclosed. Moreover, targeting either of these domains cannot simultaneously remove the methyltransferase activity and chromatin binding function of NSD2.…”
Section: Introductionmentioning
confidence: 99%